Management of Amiodarone-Induced Thyrotoxicosis at a Cardiac Transplantation Centre - Isaacs, Michelle; Costin, Monique; Bova, Ron; Barrett, Helen L.; Heffernan, Drew; Samaras, Katherine; Greenfield, Jerry R. (Frontiers in Endocrinology, 2018)
Background: Amiodarone-induced thyrotoxicosis (AIT) is associated with significant morbidity and mortality, particularly in patients with cardiac failure. The aim of the study was to evaluate the management of AIT at a tertiary hospital specialising in cardiac failure and transplantation. Methods: Retrospective audit of 66 patients treated for AIT by Endocrinology (2007-2016), classified as type 1 (T1) or type 2 (T2) based on radiological criteria. Main outcome measurements were response rate to initial treatment, time to euthyroidism, and frequency/safety of thyroidectomy. Results: Mean age was 60 ±2 y; 80% were male. Sixty-four patients commenced medical treatment: thionamides (THIO) in 23, glucocorticoids (GC) in 17 and combination (COMB) in 24. Median thyroxine (fT4) was 35.1 (31.2 - 46.7) in THIO, 43.1 (30.4 - 60.7) in GC and 60.0 (39.0 - >99.9) pmol/L in COMB (p=0.01). Initial therapy induced euthyroidism in 52%: 70% THIO, 53% GC and 33% COMB (p=0.045) by 100 (49 - 167), 47 (35 - 61) and 53 (45 - 99) d respectively (p=0.02). A further 11% became euthyroid after transitioning from monotherapy to COMB. Thyroidectomy was undertaken in 33%. Patients who underwent thyroidectomy were younger (54 ± 3 vs 63 ± 2 y; p=0.03), with higher prevalence of severely impaired left ventricular function prior to diagnosis of AIT (38% vs 18%; p=0.08). Despite median American Society of Anesthesiologists classification 4, no thyroidectomy patient experienced cardiorespiratory complications/death. Conclusions: Patients with AIT had limited response to medical treatment. The poorest response was observed in COMB group, likely related to greater hyperthyroidism severity. Thyroidectomy is safe in patients with severe cardiac failure if performed in a centre with cardiac anaesthetic expertise. There should be low threshold for proceeding to thyroidectomy in patients with severe AIT and/or cardiac failure.